Peningkatan Pemahaman Dongeng Anak Tunarungu melalui Simulation Based Learning - Endang Sri Handayani (The Center for Disability Studies and Services Brawijaya University, 2017)
The research aims to determine the influence of application simulation based learning toward understanding of fairy tale for children with hearing impairment in third grade at SLB-B YRTRW Surakarta 2016/2017 academic year. This research uses a quantitative approach to research methods of experimental type of pre-experimental form one group pretest-posttest design. Subjek in this research were students in third grade at SLB-B YRTRW Surakarta 2016/2017 academic year as many as four students. Data collection techniques in this research is an objective test in multiple choice. Data analysis techniques in this research is the analysis of non-parametric Wilcoxon Signed Rank test (Wilcoxon Signed Rank Test) using SPSS versi 22. From the result of calculations using SPSS versi 22, the known value of the average posttest research sample increased. Descriptive analysis result obtained by the average value of 77,5 posttest greater than the value pretest 57,5. Non-parametric analysis result obtained count value Z= -2,000 with Asymp. Sig. (2-tailed) = 0,046 at significance level (Î±) of 5%. Based on the results of data analysis can be concluded that effect of application simulation based learning is positive toward understanding of fairy tale for children with hearing impairment in third grade at SLB-B YRTRW Surakarta 2016/2017 academic year.